Cultural transmission and extortion - Garret Ridinger (Games, 2018)
This paper explores the role of cultural transmission in extortion. Extortion is modeled as an asymmetric contest where individuals from one group attempt to take from individuals in another group. Using a model of cultural transmission, this paper finds the existence of a unique asymptotically stable equilibrium where there are a fraction of people who defend against extortion and a fraction of people who take from others. The degree of extortion is decreased when: (1) extortion is less effective; (2) socialization efforts of parents who resist are more effective; and (3) socialization efforts of parents who abstain from extortion are more effective. A key finding is the existence of a complementarity between the effectiveness of socialization. When socialization is more effective for resisting extortion and choosing not to extort, there is a much larger reduction of extortion than either increase could achieve alone. This provides a potential explanation for why some countries like Singapore and Hong Kong were able to greatly reduce corruption and suggests potential policy applications.
Keywords: 330; cultural transmission; evolutionary game theory; contests; extortion; corruption